Clinical Features of Ocular Toxocariasis in Adult Korean Patients. (3rd March 2016) - Jee, Donghyun; Kim, Kyu Seop; Lee, Won Ki; Kim, Wungjae; Jeon, Sohee
Abstract: Purpose : To investigate the clinical characteristics and treatment results of adult patients with ocular toxocariasis. Methods : A total of 54 consecutive patients who were clinically and serologically diagnosed with ocular toxocariasis were retrospectively reviewed. Results : Among patients, 66.7 and 77.3% showed increases in eosinophil cationic protein (ECP) and total Ig E in serum, respectively. Four eyes (7.2%) initially presented as neuroretinitis with subsequent motile retinal lesion. The recurrence rates in the combination treatment group with albendazole and corticosteroids were significantly lower than those in the steroid-alone group during the mean follow-up of 27.6 months ( p  = 0.001). Conclusions : The adjunctive test of serum total IgE level may be helpful for the diagnosis of ocular toxocariasis. Ocular toxocariasis should be considered in the differential diagnosis of unilateral neuroretinitis with subsequent motile retinal lesion. Combined treatment with albendazole and corticosteroids appeared to be effective for reducing the recurrence of intraocular inflammation.